Graphene‐Armored Aluminum Foil with Enhanced Anticorrosion Performance as Current Collectors for Lithium‐Ion Battery. Issue 47 (27th October 2017) - Wang, Mingzhan; Tang, Miao; Chen, Shulin; Ci, Haina; Wang, Kexin; Shi, Liurong; Lin, Li; Ren, Huaying; Shan, Jingyuan; Gao, Peng; Liu, Zhongfan; Peng, Hailin
Abstract: Aluminum (Al) foil, as the most accepted cathode current collector for lithium‐ion batteries (LIBs), is susceptible to local anodic corrosions during long‐term operations. Such corrosions could lead to the deterioration or even premature failure of the batteries and are generally believed to be a bottleneck for next‐generation 5 V LIBs. Here, it is demonstrated that Al foil armored by conformal graphene coating exhibits significantly reinforced anodic corrosion resistance in both LiPF6 and lithium bis(trifluoromethanesulphonyl) imide (LiTFSI) based electrolytes. Moreover, LiMn2 O4 cells using graphene‐armored Al foil as current collectors (LMO/GA) demonstrate enhanced electrochemical performance in comparison with those using pristine Al foil (LMO/PA). The long‐term discharge capacity retention of LMO/GA cell after ≈950 h straight operations at low rate (0.5 C) reaches up to 91%, remarkably superior to LMO/PA cell (75%). The self‐discharge propensity of LMO/GA is clearly relieved and the rate/power performance is also improved with graphene mediations. This work not only contributes to the long‐term stable operations of LIBs but also might catalyze the deployment of 5 V LIBs in the future. Abstract : Conformal multilayer graphene films are synthesized onto aluminum (Al) foil via plasma‐enhanced chemical vapor deposition to reinforce its anti‐anodic corrosion performance. Thanks to its enhanced anti‐anodic corrosion property, cells utilizing graphene‐armored Al foil as cathode current collectors show remarkably improved long‐term cycling stability and relieved self‐discharge propensity. Moreover, cell's rate/power performance is also boosted with the mediation of graphene.